Students in Hungarian Higher Education and Their Perception of Dificulties During Their Studies - Hrabéczy, Anett (Central European Journal of Educational Research, 2021)
Our research aims to examine the recruitment of students who experience difficulties with learning during their higher education studies and the motives behind their career choices, as well as the correlation of these factors with student persistence. The topicality of the problem stems from the diversity of students as a result of the expansion of higher education, as well as the increasing proportion of reading comprehension and other learning difficulties that can hinder individuals’ progress in the labour market. Previous research has linked problems in learning in higher education to underdeveloped skills. However, we hypothesize that the occurrence of difficulties during students’ studies and careers is determined by career choices, which are influenced by social background. While in higher education the social status differences of the family background already seem to disappear, the origin also affects the higher education career. To test the viability of this assumption, statistical methods were used to analyze the CHERD-Hungary database PERSIST -2019. In the case of difficulties and low persistence, we found a relationship with the career choice patterns of the students studied, especially with family factors influencing career choice and students’ interest in their current education. One of our most important findings is that students who experience difficulties during learning can be divided into two groups. One group is characterized by low social status indicators, participating in low prestige and high risk fields of education, and there are specific cultural disadvantages in the background of their difficulties. The other group includes students who come from a higher-status family and concentrate on higher-risk but more prestigious courses, characterized by above-average selectivity and a higher risk of dropping out.